Instant and short-term effects of acupuncture for depression and anxiety in unstable angina pectoris patients with percutaneous coronary interventions - Pei, Juan Hui; Gan, Feng; Bai, Yun He; Xing, Yan Lin; Jia, Jian Jun; Wang, Huan (Frontiers in Cardiovascular Medicine, 2024)
Aim Patients with unstable angina pectoris (UAP) usually present anxiety or depression during percutaneous coronary intervention (PCI). This study sought to investigate the instant and short-term effects of acupuncture for anxiety and depression in UAP patients with PCI. Methods A total of 210 UAP patients who underwent PCI were recruited and randomly assigned (1:1:1) to acupuncture, placebo, or control groups. Enzyme-linked immunosorbent assay was used to detect the levels of fasting glucose, fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), interleukin-6 (IL-6), high-sensitivity C-reactive protein (Hs-CRP), advanced oxidation protein products (AoPPs), and oxidized low-density lipoprotein (OX-LDL). Serial questionnaires with the Hamilton Anxiety (HAMA) scale and the Pittsburgh Sleep Quality Index were evaluated, and heart rate variability indicators were obtained. Results Primary end-point: low frequency/high frequency (HF) was lower in the electroacupuncture group (p = 0.014), while standard deviation of normal-to-normal intervals, average standard deviation of normal-to-normal intervals, percentage of successive intervals that differ more than 50 ms, and HF were increased with acupuncture (p = 0.018, p = 0.043, p = 0.016, and p = 0.002, respectively). Secondary end-point: significant improvements in anxiety levels (HAMA) were observed in the three groups (p < 0.001). The fasting insulin and HOMA-IR levels were similar between the control group and the acupuncture group (p = 0.285 and p = 0.165, respectively). The levels of IL-6 and AoPPs differed among the three groups (p = 0.021 and p < 0.001, respectively). However, no significant differences were found in fasting plasma glucose, fasting c-peptide, Hs-CRP, and OX-LDL levels among the three groups (p = 0.585, p = 0.611, p = 0.902, and p = 0.756, respectively). Conclusions In this study, short-term acupuncture may potentially relieve clinical symptoms before PCI treatment. Clinical Trial Registration ClinicalTrials.gov, identifier (NCT03789344).